Clinical prediction rules. (7th August 2009) - Falk, Gavin; Fahey, Tom
Abstract : In this pair of articles, Gavin Falk and Tom Fahey (doi:10.1136/bmj.b2899 ) set out what to consider when using a clinical prediction rule, and Dan Mayer (doi:10.1136/bmj.b2901 ) shows how one such rule, the Ottawa ankle rules, is applied